2022
DOI: 10.1177/09544062221087547
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to increase the environmental sustainability of the discharging process in the over-injection of conduits for bowden cables using automation

Abstract: The industry of automotive components is highly competitive. Polymer injection, used to over-mould conduits, is used to produce the necessary connections between the end of the Bowden cables and the car parts where they need to be assembled. Depending on the vehicle or the use, there will be a different connection of the conduit. The industry continuously looks for greener and more sustainable solutions. This study presents a strategy to save energy in polymer over-injection moulding. The developed concept con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…All devices that directly interfered with the productivity of the equipment and that were not able to satisfy the new requirements were replaced or improved. As in works previously presented by other authors [34,[42][43][44]46,47,[65][66][67], the choice to solve the problems identified essentially involved the adoption of conventional automation driven by programmable devices, to the detriment of robotics, despite initially considering the use of robotics. In fact, for situations such as the case under study, where competitiveness and a quick return on investment are crucial factors for the adoption of the developed concepts, conventional automation usually represents a more economical solution that consumes less area on the shopfloor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All devices that directly interfered with the productivity of the equipment and that were not able to satisfy the new requirements were replaced or improved. As in works previously presented by other authors [34,[42][43][44]46,47,[65][66][67], the choice to solve the problems identified essentially involved the adoption of conventional automation driven by programmable devices, to the detriment of robotics, despite initially considering the use of robotics. In fact, for situations such as the case under study, where competitiveness and a quick return on investment are crucial factors for the adoption of the developed concepts, conventional automation usually represents a more economical solution that consumes less area on the shopfloor.…”
Section: Discussionmentioning
confidence: 99%
“…This At the injection machine level, the main idea is to use the equipment typically used (Figure 15). The main reason was the cost, as the latest versions of these machines cost more than EUR 20,000, and it is possible to restore and upgrade existing machines for a small fraction of this price, thus contributing to the reuse of equipment, avoiding their landfilling and the respective environmental consequences [36,65]. This sub-equipment was placed on rails, in order to facilitate access to its components for maintenance purposes.…”
mentioning
confidence: 99%
“…Additionally, this alloy is highly resistant to corrosion and wear, making it an ideal material for high-T and high-pressure moulding applications; Fe-Ni36 or INVAR-36 ® is commonly used in injection moulds. These materials are known for their low thermal expansion coefficient (α), meaning they maintain their dimensional stability even when exposed to T changes, and heat-treated (HT) steels are ideal for high-volume moulding applications where durability is critical [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The closure of the male mold involves high forces [15], rendering the manual retrieval of items from the female mold extremely perilous [16]. Therefore, for both safety and production capacity considerations, this operation necessitates automation [17][18][19]. Given its multifaceted motion requirements, including the retrieval of plastic items from the male mold and their placement on an external conveyor [20], Cartesian Robots emerge as a highly suitable solution [21].…”
Section: Introductionmentioning
confidence: 99%